Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1162/pres_a_00216
|View full text |Cite
|
Sign up to set email alerts
|

Driving for Real or on a Fixed-Base Simulator: Is It so Different? An Explorative Study

Abstract: International audienceThe use of driving simulators to assess driving abilities is often controversial because of their artificiality. Our aim is thus to tackle this question by estimating and comparing new indicators such as the mental workload, the psychological feeling (e.g., stress, anxi- ety, pleasure, and mastery), and feeling of presence when driving a simulator and a real vehicle (either one’s own or one that belongs to a driving school). We are most inter- ested in a particular sort of real-world driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 36 publications
(49 reference statements)
1
18
0
Order By: Relevance
“…A recent investigation of driving in real and simulated environments reported considerable similarity in the structure of individual task workload responses for simulated and real-world driving. 47 Encouragingly, findings from the same study indicated that there was no significant difference for stress response between driving in a simulated environment, and driving in one's own vehicle. 47 …”
Section: Discussionmentioning
confidence: 96%
“…A recent investigation of driving in real and simulated environments reported considerable similarity in the structure of individual task workload responses for simulated and real-world driving. 47 Encouragingly, findings from the same study indicated that there was no significant difference for stress response between driving in a simulated environment, and driving in one's own vehicle. 47 …”
Section: Discussionmentioning
confidence: 96%
“…All these limitations are necessary and legitimate, but they confine user tests to experts in the field and keep final users distant from them. Driving simulators reduce this gap, but, although their effectiveness has been proven for traditional cars [29], very little is known about their validity when the level of automation increases.…”
Section: Wizard Of Oz For Autonomous Drivingmentioning
confidence: 99%
“…When it comes to Driving Simulation (DS), VR is used to study several aspects of the driving task. In this context, moving-base simulators [10] are preferable to fixedbase simulators [11,12] for their closer approach to realworld driving [13]. By investigating the physical, behavioral and cognitive validity of these kind of simulators with respect to the real driving task [11], it has been also shown that DS can be a useful tool for the initial resumption of driving, because it helps to avoid stress that may lead to task failure or deterioration in performance.…”
Section: Related Workmentioning
confidence: 99%